1988
DOI: 10.2307/3899167
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Infiltrability of Semiarid Mountain Slopes

Abstract: The objective of tbis research was to determine the effects of selected vegetation, soil, rock, and slope variables on lnflltration of semiarid rangelands with slope gradients ranghtg from g-70%. Analyses were made on 2 sets of data collected a year apart in the Guadalupe Mountains of New Mexico and consisted of Pearson and partial correlation analysis of the dependent infiltration variables and independent site variables. In addition, htfiltratioa was regressed against uncorreiated factors produced by factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
0
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(67 citation statements)
references
References 16 publications
5
60
0
2
Order By: Relevance
“…The threshold indicated that small stone contents, which usually also are associated with small and rounded stones, did not exhibit this effect. In this case it can be expected that the small stones are embedded within the soil matrix and may even decrease infiltration rates (Wilcox et al, 1988). This threshold agrees with the calculation of soil erodibility in the revised universal soil loss equation, which also uses a threshold of 10 % for the consideration of stones (Roemkens et al, 1997).…”
Section: Initial Abstractionsupporting
confidence: 80%
“…The threshold indicated that small stone contents, which usually also are associated with small and rounded stones, did not exhibit this effect. In this case it can be expected that the small stones are embedded within the soil matrix and may even decrease infiltration rates (Wilcox et al, 1988). This threshold agrees with the calculation of soil erodibility in the revised universal soil loss equation, which also uses a threshold of 10 % for the consideration of stones (Roemkens et al, 1997).…”
Section: Initial Abstractionsupporting
confidence: 80%
“…These degraded areas are characterized by soil truncation and often by outcrops of weathered bedrock. These structurally degraded soils limit soil biological activity and plant establishment by reducing plant root development and growth, and by reducing water and nutrient cycling and storage capacity (Wilcox et al, 1988;McGinty et al, 1995). Degraded land has generally a low vegetative cover (18% ± 23.5), and low soil organic matter content (1% ± 1).…”
Section: Effect Of Land Use and Management On Runoff Generationmentioning
confidence: 99%
“…since the plant colonized the site). Several authors have underlined the lack of data concerning the individual response of the most representative species of the Mediterranean matorral to water erosion processes and also the relative importance of plant components in water erosion control (Rickson and Morgan, 1998;Wilcox et al, 1988;Cabezas et al, 1990;Sala and Calvo, 1990). Furthermore, the majority of existing studies on vegetation±erosion relationships in the Mediterranean region have been carried out in the short term, that is during specific natural or simulated rainfall events.…”
Section: Introductionmentioning
confidence: 99%